Credence goods markets, distributional preferences and the role of institutions - Dominik Erharter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
We study credence goods markets where an expert not only cares for her own monetary payoff, but also for the monetary payoff of her customer. We show how an expert with heterogeneous distributional preferences responds to monetary incentives in the absence of institutions, under liability and/or verifiability and identify optimal contracts for an expert with distributional preferences in each of these settings.
Keywords: D63; D64; L13; L15; C72; 330; other-regarding preferences; credence good; institution; contract theory; industrial organization